Peran Beasiswa Karawang Cerdas dalam Membentuk Sikap Tanggung Jawab dan Motivasi Belajar Siswa pada Mata Pelajaran PAI Kelas Xi di MAN 2 Karawang - Muhammad Nasai Dwi Saputra; Achmad Junaedi Sitika; Agus Susilo Saefullah (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study examines the role of the Karawang Cerdas Scholarship in fostering students’ responsibility and learning motivation in Islamic Religious Education (PAI) among 11th-grade students at MAN 2 Karawang. The study was motivated by the importance of developing responsibility and learning motivation as essential objectives of Islamic education while exploring the scholarship’s contribution beyond financial assistance. A qualitative case study approach was employed, with data collected through interviews, observations, and documentation involving scholarship recipients, PAI teachers, and program administrators. Data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings indicate that the Karawang Cerdas Scholarship strengthens students’ academic responsibility, discipline, compliance with school regulations, awareness of maintaining the school’s reputation, and accountability in utilizing scholarship funds through the Statement of Absolute Responsibility (SPTJM). The program also enhances learning motivation, reflected in increased enthusiasm, active classroom participation, sustained academic achievement, and clearer educational goals. These improvements contribute to higher attendance, better PAI learning outcomes, fewer disciplinary violations, and the development of positive character traits. The study concludes that the Karawang Cerdas Scholarship functions not only as financial assistance but also as an effective instrument for character development and learning motivation.